Implementasi Kriptografi Metode Elgamal Untuk Keamanan Data Teks - Muhamad Akbar; Indra Kanedi; Ockhy Jey Fhiter.W (UNIVED Press, 2025)
The development of technology and information today greatly affects data security and privacy. Data, which includes facts or details about an event, can be in various forms and requires reliable management. Cryptography is the main solution to securing information, which involves two main processes: encryption and decryption. The ElGamal method, an asymmetric cryptography algorithm, uses a pair of public and private keys, increasing data security without sharing the secret key. ElGamal's strength lies in the Discrete Logarithm Problem, which provides resistance to brute force attacks. It can also be used for digital signatures, ensuring the authenticity and integrity of dataThe implementation results concluded that ElGamal effectively secures text data by encrypting it into a sequence of unrepresentative characters. This implementation provides an additional layer of security by making the encrypted data unconnected to the original information